2012
DOI: 10.4012/dmj.2011-142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blood contamination before or after surface treatment on adhesion of 4-META/MMA-TBB resin to root dentin

Abstract: The purpose of this study was to evaluate the influence of blood contamination before or after surface treatment on adhesion of 4-META/MMA-TBB resin. After bovine root dentin surfaces were contaminated with blood before or after dentin surface treatment with 10-3 solution, the contaminated surface was rinsed with water, air-dried, or re-treated with 10-3 solution. Dye leakage and microtensile bond strength (MTBS) of 4-META/MMA-TBB resin to dentin were measured after storage in water for 24 h. When blood contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Takefu et al [ 26 ] (B#1) reported that the leakage value and micro-tensile bond strength were restored to an uncontaminated group after re-treating the surface with 10-3 solution (10% citric acid [pH 0.86] and 3% ferric chloride) and rinsing with water; however, re-etching by phosphoric acid after saliva contamination reduced the bond strength, as mentioned in a previous section ( 3.2 . Saliva contamination).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Takefu et al [ 26 ] (B#1) reported that the leakage value and micro-tensile bond strength were restored to an uncontaminated group after re-treating the surface with 10-3 solution (10% citric acid [pH 0.86] and 3% ferric chloride) and rinsing with water; however, re-etching by phosphoric acid after saliva contamination reduced the bond strength, as mentioned in a previous section ( 3.2 . Saliva contamination).…”
Section: Resultsmentioning
confidence: 87%
“…A total of 52 papers were identified (from 1990 to 2020), 39 of which were excluded after a review (about adhesives, not using resin cement: 20 papers; not including bond strength test: 4 papers; review without any data: 3 papers; no examination of decontamination or simple explanation of the contamination effects of decreased bond strength: 10 papers; and using glass ionomer cement: 2 papers). We also included six papers found in a manual search, resulting in a total of 19 articles for inclusion in this review [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] ] ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…This may be because of effective and sufficient resin-impregnated layer formations by UB applications on bonding durability and stability [ 22 , 23 ]. Furthermore, the tooth surface treatments using 10-3 solutions and EDTA were more effective compared with phosphate solution in removing contaminants and thin layers of cutting debris (smear layers) without excess dentin decalcification [ 24 , 25 , 26 ], which may have improved the bond strength. When performing adhesive restoration methods for vertically fractured roots followed by intentional replantation in a clinical setting, blood contamination for the fractured root surface is assumed.…”
Section: Discussionmentioning
confidence: 99%
“…When performing adhesive restoration methods for vertically fractured roots followed by intentional replantation in a clinical setting, blood contamination for the fractured root surface is assumed. However, a previous study reported that the µTBS of the contaminated dentin after treatment with 10-3 solution was equivalent to that of noncontaminated dentin [ 24 ]. Therefore, using 10-3 solution may be beneficial in adhesive restoration methods.…”
Section: Discussionmentioning
confidence: 99%
“…During fabrication and trial fitting of prosthetic restorations, abutment surfaces, such as dentin, restorative materials, and core foundation materials, may be contaminated by saliva and blood 3,4) . Therefore, adherent surfaces should be thoroughly cleaned and conditioned before cementation with resin luting cement to ensure long-term bonding stability 5) .…”
Section: Introductionmentioning
confidence: 99%